Hogyan válasszunk megfelelő szert? Új kérdések az áttétes melanoma kezelésében - Oláh Judit Magdolna; Gyulai Rolland Péter (2016)
The last few years brought about a complete paradigm-shift in the field of melanoma therapy: eight new drugs, including three immunooncologic, four targeted and one oncolytic virus, became available in the daily practice. These new treatments provide a significantly increased overall survival potential for patients with metastatic melanoma. Choosing the optimal treatment for the individual patient, however, requires the careful evaluation of several patient- and drug-related factors, and poses a great challenge for the oncologists. This review summarizes the practical aspects of the selection of the optimal melanoma treatment.